Resolução de problemas: uma análise das concepções de professores de matemática do ensino fundamental - FARIAS, Dione Barros (Universidade Federal de Mato Grosso, 2022)
The Problem Solving from the official documents and international , comes consolidating as important for the field of Mathematics Education. In this perspective, we aim analyze what are the senses attributed by mathematics teachers to Problem Solving. Regarding the theme, there are several focuses and approaches, of which we highlight authors like Polya, Vila and Callejo, Onuchic and Allevato, Schoenfeld, among others, who we resort as theoretical support. An investigation was carried out with seven mathematics teachers from the city of Breves - PA, who responded a semi-structured interview. We observe what conceptions that teachers mobilize in relation to Problem Solving, and as they establish a relationship with knowledge about their pedagogical practices, concepts and ideas, change their professional practices.